Phytochemical Screening and Toxicological Evaluation Using Brine Shrimp Lethality Test (BSLT) of Some Fractions of Prasman Leaves (Eupatorium triplinerve V) Extract - Kumala, Shirly; Sapitri, Dwi Windi (Indonesian Journal of Cancer Chemoprevention, 2011)
Prasman leaves (Eupatororium triplinerve V) was well documented to have anti cancer benefit in Indonesian traditional medicine history. However, there were noscientific studies including toxicological assessment on the planextract.The purpose of this study was to investigate thetoxicological effect of some fractions of Prasman leavesmethanol extract. Phytochemical screening by the Farnsworth method on powder and some fraction of the methanol extractwere conducted followed by toxicitytest using the Ã¢â¬ÅBrine Shrimp LethalityÃ¢â¬Â test (BSLT) method. In the current study results, the phytochemical screening showed the presence of flavonoid, saponin, coumarin, tannin, steroidandvolatileoil.LC50ofthen-hexanefraction238.660g/mL,ethylacetatefraction 24.420g/mL,andn3butanol64.100g/mL.